Efektifitas Penggunaan Injeksi Oksitosin pada Penanganan Perdarahan Post Partum di RSU Latersia Binjai Kec. Binjai Kota Binjai Provinsi Sumatera Utara Tahun 2024 - Kamelia Sinaga; Imran Saputra Surbakti; Lia Nurpiani; Rumondang Sitorus; Asnita Sinaga; Ribur Sinaga (Jurnal Siti Rufaidah, 2024)
Background: Postpartum hemorrhage is the main cause of maternal death in both developed and underdeveloped countries, followed by hypertension and infection. The decline in. Reducing maternal mortality must be carried out by implemnting SDGS, which is one of the targets that will be achieved. This study aims to determine the effectiveness of the use of oxytocin injection in the treatment of postpartum hemorrhage. Methods: This type of research is a descriptive study using a retrospective case control study design that aims to determine the effectiveness of the use of oxytocin injection in the treatment of post partum bleeding at Latersia Hospital Binjai District Binjai, Binjai City North Sumatra Province In 2024. part of the entire object under study and is considered to represent the entire population. In other words, the elements of the population are selected based on their ability to represent them (Setiadi 2016). This sampling uses a total sampling of 30 people. Data collection techniques use questionnaire sheets and respondent observation sheets. The data analysis technique used the Mann Whitney Test. Results: Based on the results of the Mann-Whitney test, it was obtained that p-value was 0.000 because p-value <0.05, it can be concluded that oxytocin injection is more effective in handling Post Partum Bleeding compared to no injection. Oxytocin in Post Partum Mothers at Latersia Hospital Binjai District Binjai, Binjai City North Sumatra Province In 2024. Conclusion: This study means that if given oxytocin injection is more effective in handling Post Partum Bleeding compared to not given oxytocin injection in Post Partum mothers at Latersia Hospital Binjai District Binjai, Binjai City North Sumatra Province In 2024..